Investigating Job Satisfaction Among Academic and Non-Academic Employees: Evidence from a Public University in Bangladesh - Akter, Sabina; Yesmin, Farjana; Akter, Sadia; Sakib, Md. Nazmus; Sarker, Md. Mostakim (Asosiasi Doktor Sistem Informasi Indonesia, 2025)
This study explores job satisfaction and its determinants among academic and non-academic staff at Begum Rokeya University, Bangladesh, to identify factors influencing morale, motivation, and retention in a public higher education institution. Using a mixed-methods approach, quantitative data were gathered via a structured 5-point Likert-scale questionnaire, and qualitative insights were obtained through semi-structured interviews with a purposive sample of 50 employees. Results show moderate overall job satisfaction, with high satisfaction regarding annual leave (mean = 4.32) and work environment (mean = 4.04), but low satisfaction with promotion opportunities (mean = 2.72) and training and development (mean = 2.78). The scale’s high reliability (Cronbach’s α = 0.993; standardized α = 0.994) supports the validity of the findings. Herzberg’s motivation-hygiene theory highlights promotion and professional development as key hygiene factors. This research offers crucial insights for improving promotion policies and training systems and calls for future longitudinal studies across Bangladesh’s higher education sector.